Peranan Efektif Komunikasi Kerja, Konflik Kerja, Stres Kerja dan Lingkungan Kerja dalam Menguatkan Produktivitas Karyawan Perusahaan Perak Tom’s Silver Yogyakarta - Harmen, Hilma; Syahreza, Dinasarah; Manik, Agnes Mika Cristina Br; Lubis, Ahmad Suhendri; Agustin, Amanda; Hutagalung, Ayu Triani; Ringo, Jonathan Siringo; Prayoga, Wiko (Economic Reviews Journal, 2024)
Purpose. The purpose of this research is to analyze how communication, conflict, work stress, and the work environment affect employee productivity in an organization. Methods. The research method uses a systematic approach by formulating relevant keywords to search for information about the influence of communication, conflict, work stress and the work environment on employee productivity through academic databases and trusted information sources. Findings. (1) Effective communication in the organization, which includes message understanding, conflict management, and transparency, is positively correlated with increased employee productivity; (2) Conflict in the workplace, whether interpersonal, role, or goal, can hinder cooperation, role clarity, and goal alignment, which in turn reduces employee productivity, so effective management of conflict is key in increasing their productivity; (3) Job stress, arising from excessive job demands and lack of social support in the workplace, can significantly reduce employee productivity as well as their well-being; (4) A comfortable, safe and supportive work environment has a positive influence on employee productivity, by increasing physical and psychological comfort and fulfilling basic needs that enable employees to achieve optimal work potential; and (5) Research results at the Tom's Silver Company in Yogyakarta show that communication, a good work environment, and work stress management significantly influence employee productivity, while workplace conflict has a negative impact, although not statistically significant. Implication. This research can provide insight into the factors that influence employee productivity, as well as help in designing more effective management strategies to improve organizational performance.